Introduction to private equity, debt and real assets : from venture capital to LBO, senior to distressed debt, immaterial to fixed assets - Demaria, Cyril (Hoboken : John Wiley & Sons, 2020)
"Building on and refining the content of previous editions, the third edition adopts the same logical, systematic, factual and long-term perspective on private equity, combining academic rigour with extensive practical experience. The content has been fully revised to reflect developments and innovations in the private equity sector, exploring new strategies, changes in structuring and the drive of new regulations. New sections have been added, covering fund raising and fund analysis, portfolio construction and risk measurement, as well as liquidity, and start-up analysis. In addition, private debt and private real assets are given greater focus, with two new chapters analysing the current state of these evolving sectors. The private equity sector is growing fast, from roughly $100bn of assets under management in 1990 to $2.5tn in 2017. It is also subject to great innovation, with new investment strategies, changes in structuring, and the drive of new regulations. In addition to private equity, two sectors in particular have been developing: private debt (direct lending, mezzanine/unitranche financing, distressed debt) and private real assets (private real estate, private infrastructure, natural resources, etc.) The evolution of these areas is significant -- in 2017 they represented $1.5tn of assets under management -- and should be integrated into any comprehensive book on the topic, as private companies finance through equity, debt and asset financing. Assets under management for private markets and private finance are expected to double by 2023, from $4tn to $8tn"--
Includes bibliographical references and index.
Keywords: Private equity